Lunar interior properties from the GRAIL mission. Issue 7 (14th July 2014) - Williams, James G.; Konopliv, Alexander S.; Boggs, Dale H.; Park, Ryan S.; Yuan, Dah‐Ning; Lemoine, Frank G.; Goossens, Sander; Mazarico, Erwan; Nimmo, Francis; Weber, Renee C.; Asmar, Sami W.; Melosh, H. Jay; et al.
Abstract The Gravity Recovery and Interior Laboratory (GRAIL) mission has sampled lunar gravity with unprecedented accuracy and resolution. The lunar GM, the product of the gravitational constant G and the mass M, is very well determined. However, uncertainties in the mass and mean density, 3345.56 ± 0.40 kg/m3, are limited by the accuracy of G. Values of the spherical harmonic degree‐2 gravity coefficients J2 and C22, as well as the Love number k2 describing lunar degree‐2 elastic response to tidal forces, come from two independent analyses of the 3 month GRAIL Primary Mission data at the Jet Propulsion Laboratory and the Goddard Space Flight Center. The two k2 determinations, with uncertainties of 1%, differ by 1%; the average value is 0.02416 ± 0.00022 at a 1 month period with reference radius R = 1738 km. Lunar laser ranging (LLR) data analysis determines (C − A)/B and (B − A)/C, where A < B < C are the principal moments of inertia; the flattening of the fluid outer core; the dissipation at its solid boundaries; and the monthly tidal dissipation Q = 37.5 ± 4. The moment of inertia computation combines the GRAIL‐determined J2 and C22 with LLR‐derived (C − A)/B and (B − A)/C. The normalized mean moment of inertia of the solid Moon is Is/MR2 = 0.392728 ± 0.000012. Matching the density, moment, and Love number, calculated models have a fluid outer core with radius of 200–380 km, a solid inner core with radius of 0–280 km and mass fraction of 0–1%, and a deep mantle zone of low seismic shear velocity. The mass fraction of the combined inner and outer core is ≤1.5%.